RELATIONSHIP INNOVATION WITH ORGANIZATIONAL AGILITY AMONG EMPLOYEES CASE STUDY: ISLAMIC AZAD UNIVERSITY OF KHORASGAN (ISFAHAN) (Singaporean Journal of Business Economics and Management, 2014)
The aim of the present study to assess the relationship between organizational agility with innovation among staff of the Islamic Azad University of khorasgan branch (Isfahan) in the year 2010-2011, which was performed by descriptive method, was a kind of Correlations. Statistical Society, Islamic Azad University, khorasgan Branch staff to number of 323 people who were 175 people with simple random sampling proportional to size of the selection. Data in this study, two standard questionnaire dorabji and lamli (1998 Organization innovation in the atmosphere) and enterprise agility aspaider (2007) validity of both specialists and experts with the questionnaire on desirable sustainability report was both a questionnaire using the cronbach's Alpha for the atmosphere of innovation in an organization questionnaire 0.943 organizational agility questionnaire was 0.945. In the analysis of the information for this study, two levels of descriptive statistics (mean, frequency, percentage, and LSD) and inferential statistics (Pearson, variance analysis). The results showed that between innovation and its dimensions (participation, freedom, trust, time, fun idea, and conflict, supporting the idea, talk and take risks) with organizational agility at the level of p